The effects of microenergy acoustic pulses on animal model of obesity‐associated stress urinary incontinence. Part 2: In situ activation of pelvic floor and urethral striated muscle progenitor cells. Issue 8 (27th August 2019) - Kang, Ning; Peng, Dongyi; Wang, Bohan; Ruan, Yajun; Zhou, Jun; Reed‐Maldonado, Amanda B.; Banie, Lia; Wang, Guifang; Xing, Nianzeng; Tang, Yuxin; Lin, Guiting; Lue, Tom F.
Abstract: Aim: To investigate the possibility and mechanism of microenergy acoustic pulses (MAP) for activating tissue resident stem/progenitor cells within pelvic and urethral muscle and possible mechanism. Methods: The female Zucker Lean and Zucker Fatty rats were randomly divided into four groups: ZL control, ZLMAP, ZF control, and ZFMAP. MAP was applied at 0.033 mJ/mm 2, 3 Hz for 500 pulses, and the urethra and pelvic floor muscles of each rat was then harvested for cell isolation and flow cytometry assay. Freshly isolated cells were analyzed by flow cytometry for Pax‐7, Int‐7α, H3P, and EdU expression. Meanwhile, pelvic floor muscle‐derived stem cells (MDSCs) were harvested through magnetic‐activated cell sorting, MAP was then applied to MDSCs to assess the mechanism of stem cell activation. Results: Obesity reduced EdU‐label‐retaining cells and satellite cells in both pelvic floor muscle and urethra, while MAP activated those cells and enhanced cell proliferation, which promoted regeneration of striated muscle cells of the pelvic floor and urethral sphincter. Activation of focal adhesion kinase (FAK)/AMP‐activated protein kinase (AMPK) /Wnt/β‐catenin signaling pathways by MAP is the potential mechanism. Conclusions: MAP treatment activated tissue resident stem cells within pelvic floor and urethral muscle in situ via activating FAK‐AMPK and Wnt/β‐catenin signaling pathway.